Filtration media comprising adsorbents
By adopting a double-layer fiber structure in the fiber container of the filter media and using almost no adhesive, the problem of the adhesive reducing the effectiveness of the filter media in the prior art is solved, and higher adsorbent load and filtration performance are achieved.
Patent Information
- Application Number
- CN202380060601.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-19
- Filing Date
- 2023-08-21
- Publication Date
- 2025-04-15
AI Technical Summary
In the case of using a large amount of adhesive, existing filter media will reduce porosity and overall effectiveness, resulting in a degradation of adsorbent performance.
Using a bilayer fiber container including an open phase and a second phase, the adsorbent is loaded into the open phase by using little or no adhesive in the fiber container and the release of the adsorbent is prevented by the pore-size gradient structure.
Higher adsorbent load and better filtration performance are achieved, avoiding the problem of adhesive reducing adsorbent performance, and improving the surface area utilization efficiency of the filter media.
Smart Images

Figure CN119836316A_ABST
Abstract
Description
[0001] Related Applications
[0002] This application is an international application that claims priority to U.S. Provisional Application No. 63 / 399,323, filed on August 19, 2022, which is incorporated herein in its entirety. Technical Field
[0003] The present disclosure relates to filter media and uses thereof. The present disclosure also relates to methods of producing filter media and uses of the filter media for removing gases from, for example, the purification of air. Background Art
[0004] Adsorbents such as activated carbon particles can be incorporated into filter media for a variety of purposes, including but not limited to gas adsorption filters, cabin air filters for vehicles, air intake filters for vehicles, or heating, ventilation, and air conditioning filters. For example, adsorbents can be used in filter media to remove gases, such as hazardous gases, from the air. Filter media containing adsorbents remove contaminants from fluids by surface adsorption, wherein the contaminants are attracted to the surface of the adsorbent and are held therein by physical attraction and / or chemical bonds.
[0005] In order to prevent adsorbents such as activated carbon particles from "escaping" from the filter media, an adhesive may be used to adhere the carbon layer to the fiber substrate of the filter media. Thus, the filter media layer including the adsorbent may additionally include an adhesive. However, large amounts of adhesive as used in the prior art may reduce porosity and reduce the overall effectiveness of the media.
[0006] For example, a slurry of an adsorbent and a liquid adhesive can be applied to a fibrous substrate. The slurry can form different layers on the fibrous substrate and may not be embedded in the fibrous substrate. The different layers can be separated or layered from the fibrous substrate. For example, different adhesives behave differently under different environmental conditions (e.g., temperature, pressure, etc.). Additionally, the adhesive can reduce the performance of the adsorbent, for example, by blocking the pores of the adsorbent.
[0007] There is an interest in improved filtration media and related methods of manufacture and use.
[0008] The filter media, assemblies, and methods of the present disclosure address and / or overcome opportunities for improvement. Summary of the invention
[0009] The present disclosure provides advantageous filter media, and methods for making and utilizing the same.
[0010] More specifically, the present disclosure provides an advantageous filter media comprising a fiber container comprising an open phase and a second phase disposed on the open phase; and an adsorbent disposed within the fiber container, wherein each of the open phase and the second phase comprises a specific combination of thicker fibers and thinner fibers, and wherein the average diameter of the fibers in the open phase is greater than the average diameter of the fibers in the second phase. In one or more embodiments, the thicker fibers have a thickness of 15 denier to 20 denier, and the thinner fibers have a thickness of 5 denier to 10 denier. In the present disclosure, it has been discovered that the specific ratio of thicker fibers to thinner fibers in the open phase and the second phase, as discussed in more detail below, can affect the absorbent loading and overall performance of the filter media.
[0011] The above described and other features are exemplified by the following figures and detailed description.
[0012] Any combination or permutation of the embodiments is contemplated.Additional advantageous features, functions, and applications of the disclosed filter media, assemblies, and methods of the present disclosure will be apparent from the following description, particularly when read in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] The following figures are exemplary embodiments.
[0014] Features and aspects of the embodiments are described below with reference to the drawings.
[0015] Exemplary embodiments of the present disclosure are further described with reference to the accompanying drawings. It should be noted that the various features, steps, and combinations of features / steps described below and shown in the drawings can be arranged and organized differently to produce embodiments that are still within the scope of the present disclosure. In order to assist one of ordinary skill in the art in making and using the disclosed filter media, assemblies, and methods, reference is made to the accompanying drawings, in which:
[0016] Figure 1 is a scanning electron microscope (SEM) image of the filter medium of the comparative example;
[0017] Figure 2 is an enlarged SEM image of the filter medium of the comparative example;
[0018] Figure 3 is a SEM image of the filter medium of Example 2;
[0019] Figure 4 is an enlarged SEM image of the filter medium of Example 2;
[0020] Figure 5 is a SEM image of fibers included in the open phase of the fiber container of the filter medium of Example 2;
[0021] Figure 6 is an enlarged SEM image of fibers included in an open phase of a fiber container of the filter medium of Example 2;
[0022] Figure 7 is a SEM image of fibers included in the second phase of the fiber container of the filter medium of Example 2;
[0023] Figure 8 is an enlarged SEM image of fibers included in the second phase of the fiber container of the filter medium of Example 2;
[0024] Fig. 9 is a graph of n-butane (nB) penetration (percent (%)) versus time (minutes (min)), showing nB adsorption rates of filter media of Example 1 and Comparative Examples;
[0025] Fig.10 is a graph of toluene penetration (%) versus time (minutes), showing toluene adsorption rates of filter media of Example 1 and Comparative Example;
[0026] Fig.11 is a graph of SO2 penetration (%) versus time (minutes), showing the SO2 adsorption rates of the filter media of Example 1 and Comparative Example;
[0027] Fig.12 is a graph of NO2 penetration (%) versus time (minutes), showing the NO2 adsorption rates of the filter media of Example 1 and Comparative Example;
[0028] Fig.13 is a graph of nB penetration (%) versus time (min), showing nB adsorption for the filter media of Example 2;
[0029] Fig.14 is a graph of toluene penetration (%) versus time (minutes), showing the toluene adsorption rate of the filter medium of Example 2;
[0030] Fig.15 is a graph of SO2 penetration (%) versus time (minutes), showing the SO2 adsorption rate of the filter medium of Example 2;
[0031] Fig.16 is a graph of NO2 penetration (%) versus time (minutes), showing the NO2 adsorption rate of the filter medium of Example 2;
[0032] Fig.17 is a graph of nitrogen oxide (NOx) penetration (%) versus time (minutes), showing the NOx adsorption rate of the filter medium of Example 2;
[0033] Fig.18 is a graph of NH3 penetration (%) versus time (minutes), showing the NH3 adsorption rate of the filter medium of Example 2;
[0034] Fig.19 is a graph of SO2 penetration (%) versus time (minutes), showing the SO2 adsorption rate of the filter medium of Example 3;
[0035] Fig. 20 is a graph of NOx and NO2 penetration (%) versus time (minutes), showing the NOx and NO2 adsorption rates of the filter media of Example 3;
[0036] Fig.21 is a graph of NH3 penetration (%) versus time (minutes), illustrating the NH3 adsorption rate of the filter medium of Example 3; and
[0037] Fig. 22 is a graph of NH3 penetration (%) versus time (minutes), showing a comparison of the NH3 adsorption rates of the filter media of Example 2 and Example 3. DETAILED DESCRIPTION
[0038] The exemplary embodiments disclosed herein illustrate advantageous filter media and methods / techniques thereof. However, it should be understood that the disclosed embodiments are merely examples of the present disclosure, which may be embodied in various forms. Therefore, the details disclosed herein with reference to exemplary filter media and related assembly and use processes / techniques should not be construed as limiting, but merely as a basis for teaching those skilled in the art how to make and use the advantageous filter media and / or alternative filter media of the present disclosure.
[0039] The term "nonwoven" refers to a collection of fibers in a web or mat that may be randomly interlocked, entangled, and / or bonded to form a self-supporting structural element.
[0040] "Synthetic fibers" refer to fibers made from fiber-forming materials including polymers synthesized from compounds and modified or converted natural polymer materials. Such fibers can be produced, for example, by melt spinning, solution spinning or solvent spinning.
[0041] Exemplary synthetic fibers suitable for the present disclosure are polyesters (e.g., polyalkylene terephthalates, such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.), polyalkylenes (e.g., polyethylene, polypropylene, etc.), polyacrylonitrile (PAN), and polyamides (nylons, such as nylon-6, nylon 6,6, nylon-6,12, etc.). In one embodiment, the synthetic fiber can be a bicomponent sheath-core fiber, such as PE-PP fiber, PP-PET fiber, and low-melting PET-PET fiber, or a combination thereof. In one embodiment, the sheath can include a PET copolymer (co-PET), for example, the bicomponent sheath-core fiber can be a co-PET-PET fiber. The bicomponent fiber can have a sheath with a lower melting point and a core with a higher melting point.
[0042] The term "adsorption" may be used to refer to the adsorption of a substance (such as a gas) to an adsorbent, and thus a filter containing an adsorbent may be referred to as an "adsorption" filter.
[0043] The phrase "spunbond fibers" refers to fibers formed by a process in which fibers are formed by extruding a molten thermoplastic polymer material from a plurality of fine capillaries of a spinneret and then rapidly reducing the diameter of the extruded fibers by stretching. The spunbond fibers may be randomly deposited on a collecting surface such as a mesh screen or belt. The phrase "spunbond nonwoven" refers to a nonwoven comprising spunbond fibers that may be bonded by methods such as hot calendering, by air bonding (which may be applicable to multicomponent spunbond nonwovens), or by passing the nonwoven through a saturated steam chamber at high pressure.
[0044] The phrase "meltblown fibers" refers to fibers formed by a process in which hot compressed air is applied directly at the outlet of a die. Thus, the diameter of the fibers obtained is smaller than that of spunbond fibers. The process for forming meltblown fibers may not include a separate bonding step, and the meltblown fibers are hot enough at the outlet of the die to bond when deposited on the forming mat.
[0045] Advantageous filter media and related methods of making and using the same are disclosed herein.The present disclosure provides improved filter media and improved methods for utilizing and making filter media.
[0046] The present disclosure provides an advantageous filter medium, which includes a fiber container, the fiber container including an open phase and a second phase located, for example, near or directly on the open phase; and an adsorbent, the adsorbent is located within the fiber container, wherein each of the open phase and the second phase includes thicker fibers and thinner fibers, and wherein the average pore size of the open phase is larger than the average pore size of the second phase.
[0047] The inventors surprisingly discovered that by using a double layer fiber "container" comprising an open phase and a second phase, a greater amount of adsorbent can be included within the fiber container. It is believed that the open phase structure allows the adsorbent to be loaded into the open phase and penetrate into the thickness of the material, rather than being concentrated on the surface of the container. This allows for the loading of greater amounts of adsorbent, for example, greater than 500 g / m 2 In addition, the tighter structure based on the ratio of thicker fibers to thinner fibers in the second phase prevents the adsorbent from being released from the pores. Little or no adhesive may be provided in the fiber container (e.g., on the fiber container) to keep the adsorbent in the fiber container (e.g., in the open phase), which increases the effective utilization of the surface area of the filter media and produces better filtration performance. In one embodiment, the amount of adhesive provided in the fiber container (e.g., provided to the fiber container) is less than 10 weight percent (wt%) based on the total weight of the adsorbent. In one embodiment, 0 wt% of adhesive is used in the fiber container (e.g., provided to the fiber container) based on the total weight of the adsorbent. The use of little or no adhesive provides improved performance.
[0048] Little or no use of binder allows for better performance. The disclosed filter media can achieve equivalent or better performance than filter media with more binder (which can affect gas adsorption performance). The gas adsorption performance of the adsorbent may be reduced due to the reduction of the surface area of the adsorbent caused by the liquid binder (e.g., pore clogging or coating). In addition, the liquid binder may clog the fiber substrate. For example, Figure 1 A filter medium is shown with a liquid binder (arrows) covering activated carbon particles.
[0049] Little or no use of a binder may also allow for the use of different adsorbents, depending on the desired properties and end use of the filter media. The choice of adsorbent may be tailored to the desired properties and end use of the filter media, as interactions between the binder and the adsorbent (e.g., pore blocking or covering of the adsorbent by the binder) may be minimized or absent.
[0050] The pore size gradient between the open phase and the second phase results in more efficient adsorbent loading, utilization, distribution, or a combination thereof, across the thickness of the fiber container, resulting in improved performance due to more efficient utilization of the surface area for filtration. The average pore size of each of the open phase and the second phase may be a result of the amount of different fiber sizes (e.g., denier, diameter, or a combination thereof) in each of the phases. The open phase may include fewer pores than the second layer, but the pores of the open phase may be larger than the pores of the second phase, e.g., the average pore size of the open phase may be larger than the average pore size of the second phase.
[0051] The retention of the adsorbent is due to the asymmetric / gradient fiber structure of the media. For example, the pore size gradient provided by the more compact second phase over the open phase can help retain a large amount of the adsorbent within the fiber container and prevent a large amount (e.g., a majority) of the adsorbent from accumulating on the surface of the fiber container opposite the surface to which the adsorbent is added. For example, the presence of a large amount of adsorbent at the surface of the fiber container may cause such surface of the fiber container to delaminate from a covering layer laminated to the surface of the fiber container, or cause an asymmetric structure of the filter media, which may adversely affect the pleating process of forming the filter media.
[0052] In one embodiment, the average pore size of the open phase is greater than the average pore size of the second phase. In one embodiment, the proportion of thicker fibers in the open phase is less than or equal to the proportion of thinner fibers in the open phase. In one embodiment, the proportion of thicker fibers in the second phase is less than the proportion of thinner fibers in the second phase. In one embodiment, the proportion of thicker fibers in the open phase is greater than the proportion of thicker fibers in the second phase. In one embodiment, the proportion of thinner fibers in the open phase is less than the proportion of thinner fibers in the second phase. As used herein, proportion may refer to the weight percentage of the stated fiber type relative to the total fiber weight in the stated phase.
[0053] The fiber container may have a 30 g / m2 (g / m 2 ) to 120 g / m2, for example, 60 g / m 2 Up to 90g / m 2 The fiber container may include 50 wt % to 70 wt % of the open phase and 30 wt % to 50 wt % of the second phase based on the total weight of the fiber container.
[0054] In one embodiment, the thicker fibers are present in the open phase in an amount of 30 wt% to 50 wt%, based on the total fiber weight of the open phase. In one embodiment, the thicker fibers include fibers of 15 to 20 deniers. In one embodiment, the thinner fibers are present in the open phase in an amount greater than or equal to 50 wt%, for example, 50 to 70 wt%, based on the fiber weight of the open phase. In one embodiment, the thinner fibers include fibers of 5 deniers to less than 10 deniers or fibers of 7 deniers to less than 10 deniers. In one embodiment, the thicker fibers are present in the second phase in an amount of 10 to 20 wt%, based on the fiber weight of the second phase. In one embodiment, the thinner fibers are present in the second phase in an amount of 80 to 90 wt%, based on the fiber weight of the second phase. In one embodiment, the thinner fibers are present in the second phase in an amount greater than or equal to 50, based on the fiber weight of the second phase.
[0055] Based on the total weight of the open phase, the open phase can include 30wt% to 50wt% of synthetic fibers of 15 to 20 deniers and 50wt% to 70wt% of synthetic fibers of 5 to less than 10 deniers, for example, 7 deniers to less than 10 deniers. Based on the total weight of the second phase, the second phase can include 10wt% to 30wt% of synthetic fibers of 10 to 20 deniers and 70wt% to 90wt% of synthetic fibers of 5 to less than 10 deniers, for example, 7 deniers to less than 10 deniers. Denier can be measured by ASTM D-1577.
[0056] The fibers included in the fiber container can include low-melting point fibers, for example, in an amount greater than or equal to 50 wt%, or 50 wt% to 70 wt%, based on the total fiber weight of the fiber container. As used herein, the phrase "low-melting point fibers" can refer to bicomponent sheath-core fibers having a low-melting point sheath and a higher melting point core.
[0057] In one embodiment, the thicker fibers include polyethylene terephthalate fibers. In one embodiment, the thinner fibers include polyethylene terephthalate fibers.
[0058] In one embodiment, the fibers included in the fiber container may include conventional PET fibers, for example, in an amount less than or equal to 50 wt%, or 30 wt% to 50 wt%, based on the total weight of the PET fibers (e.g., based on the total weight of the conventional PET fibers and the low-melting PET fibers). As used herein, "conventional" PET fibers may have a single component having a melting point of about 265°C.
[0059] The fiber container including the open phase and the second phase can be a thermally bonded nonwoven, for example, the open phase and the second phase can be thermally bonded to each other. The filter medium can include at least one additional spunbond nonwoven laminated on at least one surface of the fiber container. In one embodiment, the filter medium can include an additional spunbond nonwoven laminated on an opposing surface of the fiber container to prevent the adsorbent from being released from the surface of the fiber container.
[0060] A fiber container including an open phase and a second phase can be made from two carding machines. The open phase and the second phase formed by the two carding machines can be fed into a belt hot air dryer and merged into the fiber container. The second phase can be placed on the belt surface to create pores smaller than the open phase. Any suitable type of air-through dryer can be used to bond the two layers, for example, a belt air-through dryer can be used to make a fiber container with a pore size gradient.
[0061] In order to insert the adsorbent into the fiber container, the adsorbent can be dispersed on the open phase in one step. In one embodiment, the adsorbent can be dispersed in multiple steps. However, even if the adsorbent is dispersed in multiple steps, the container structure should be advantageously selected so that the first dispersed adsorbent does not remain only on the open phase, preventing the next adsorbent from entering the interior of the fiber container.
[0062] The adsorbent can be greater than 50g / m 2 , for example, greater than 100 g / m 2 , greater than 200g / m 2 , greater than 300g / m 2 , greater than 500g / m 2 Or more than 600g / m 2 In one embodiment, the adsorbent is present in an amount of less than 1,000 g / m 2 , for example, less than 900g / m 2 Or less than 800g / m 2 In one embodiment, the adsorbent is present in an amount of 50 g / m 2 Up to 1,000g / m 2 , for example, 500g / m 2 Up to 900g / m 2 or 600g / m 2 Up to 800g / m 2 The amount exists.
[0063] Exemplary adsorbents for the disclosed filter media include particles such as activated carbon particles, silica, zeolites, molecular sieves, clays, alumina, sodium bicarbonate, ion exchange resins, catalysts including enzymes, metal oxides, air fresheners or aroma particles (such as titanium dioxide), or combinations thereof. Antifungal particles can be incorporated into the filter media, such as for automotive climate control systems to remove mold and mold odors from the circulating air. Biocidal particles, virucidal particles, or combinations thereof can be incorporated into the filter media.
[0064] In one embodiment, the adsorbent comprises activated carbon particles, silica, zeolite, molecular sieve, clay, alumina, sodium bicarbonate, ion exchange resin, catalyst or a combination thereof. In one embodiment, the adsorbent comprises activated carbon particles. In one embodiment, the adsorbent comprises activated carbon particles and ion exchange resin. Ion exchange resin can help, for example, NH3 adsorption.
[0065] In one embodiment, the activated carbon particles include activated carbon powder, for example, a powder formed from particles with an average particle size in the range of 0.05 millimeters (mm) to 1.5 millimeters (e.g., 0.1 mm to 1.5 mm, 0.15 mm to 1.0 mm, or 0.3 mm to 1.0 mm). The activated carbon particles can be impregnated, for example, with an acid or a base to adsorb alkaline gases or acidic gases, respectively. For example, the activated carbon particles can be impregnated with H3PO4 (phosphoric acid) (e.g., in an amount of 20 wt% based on the total weight of the impregnated activated carbon particles) or KI (potassium iodide) (e.g., in an amount of 3 wt% based on the total weight of the impregnated activated carbon particles). In one embodiment, the adsorbent includes different impregnated activated carbon particles, for example, activated carbon particles impregnated with H3PO4 and activated carbon particles impregnated with KI. In one embodiment, the adsorbent includes impregnated activated carbon particles and an ion exchange resin. In one embodiment, the activated carbon may have a size of 20 mesh to 80 mesh, for example, a diameter of 0.17 mm to 0.85 mm.
[0066] Including different adsorbents, such as activated carbon particles, impregnated activated carbon particles, ion exchange resins, or combinations thereof can allow a single filter medium to treat (e.g., filter) multiple (e.g., two, three, four, or more than four) different compounds, such as volatile organic compounds (VOCs), and achieve fine particle levels. For example, a filter medium including different adsorbents can allow achieving at least two particle efficiencies of 99.5% at 20 centimeters per second (cm / s) (DIN 71460-1) on 0.3 micrometer (μm) NaCl, achieving a target n-butane initial penetration of 1% at 10 cm / s (DIN 71460-2), achieving a target SO2 initial penetration of 1.5% at 10 cm / s (DIN 71460-2), achieving a target NOx initial penetration of 0% at 10 cm / s (DIN 71460-2), or achieving a target NH3 initial penetration of 0% at 10 cm / s (DIN 71460-2).
[0067] In one embodiment, the adsorbent may include zeolite, alumina, ion exchange resin, or a combination thereof. The zeolite, alumina, ion exchange resin, or a combination thereof may have a molecular weight of 0.5 g / m3 (g / cm 3 ) to 0.7 g / m3 and a size of 20 to 80 mesh. In one embodiment, such adsorbents can be used alone or in a mixture with activated carbon particles. In one embodiment, a mixture of modified (e.g., impregnated) activated carbon and ion exchange resins can provide improved gas adsorption characteristics.
[0068] The process of forming the disclosed filter media can include forming a thermally bonded fiber "container" by bonding / combing an open phase and a second phase together. A first card can form the open phase, and a second card can form the second phase.
[0069] Forming the fiber container may include intermixing thicker fibers and thinner fibers in the open phase and the second phase. The open phase and the second phase may be needled to each other, such as needle-punched. In one embodiment, the open phase and the second phase may be thermally bonded by air through a dryer.
[0070] In one embodiment, the disclosed filter media can be formed by a process comprising forming a fiber container; providing an adsorbent to the fiber container; and laminating the fiber container to form the filter media. In one embodiment, the process further comprises providing an adhesive to the fiber container after adding the adsorbent to the fiber container.
[0071] In one embodiment, the binder comprises a powder. In one embodiment, the binder comprises a web. In one embodiment, no binder is present in the second phase. In one embodiment, less than 1 wt% binder is present in the second phase based on the total weight of the second phase. The amount of binder can be determined, for example, by pyrolysis gas chromatography / mass spectrometry (GC-MS). In one embodiment, forming the fiber container comprises intermixing thicker fibers and thinner fibers in the open phase and the second phase.
[0072] The open phase can be oriented on top of the second phase. When the adsorbent is provided (e.g., dispersed) onto the fiber container, gravity can help the adsorbent fall into the open phase of the fiber container. The pore size gradient can help retain larger adsorbent particles at the top surface of the fiber container and allow smaller adsorbent particles to fall further into the fiber container.
[0073] In one embodiment, the filter media further comprises a cover layer. In one embodiment, the cover layer comprises spunbond fibers. In one embodiment, the cover layer comprises an electrostatically charged layer, for example, an electrostatically charged meltblown nonwoven. The binder present in the filter media may also be present only at the interface between the fiber container and the cover layer, for example, after the binder is applied to the fiber container, the binder may not enter the fiber container.
[0074] The opposing surface of the fiber container can be laminated with a spunbond nonwoven as a cover layer. The spunbond nonwoven can prevent the adsorbent from being released from the surface of the fiber container (e.g., leaving the surface of the fiber container). Exemplary methods for laminating the spunbond nonwoven to the fiber container include hot melt spray lamination, hot melt powder lamination, and hot melt web lamination. In one embodiment, the thickness of the fiber container may not decrease during lamination. If the thickness of the fiber container is excessively reduced during lamination, the fiber container may not function properly to accommodate the adsorbent.
[0075] The spunbond nonwoven used for lamination to the fiber container can be relatively thin and have good air permeability. For example, the spunbond nonwoven can include 10 g / m 2 Up to 40g / m 2 In one embodiment, the spunbond nonwoven fabric may include 15 g / m 2 Up to 30g / m 2 PP or PET spunbond fibers. The spunbond nonwoven can have a thickness of 0.10 mm to 0.40 mm. In one embodiment, a spunbond nonwoven having a thickness of 30 g / m 2 Up to 70g / m 2 A calendered thermally bonded nonwoven of a basis weight and a thickness of 0.20 mm to 0.40 mm, rather than a spunbond nonwoven, is laminated to the fiber container.
[0076] The spunbond nonwoven may include one or more additive components. The additive component may be, for example, a dye, which may be necessary to give the filter a favorable appearance; a fiber retaining agent; a separation aid (e.g., a silicone additive and related catalyst); a fire retardant or flame retardant; a hydrophilic agent or a hydrophobic agent; a wetting agent; an antistatic agent; an antimicrobial agent; or a combination thereof. If present, the amount of these additives included may be greater than 0 wt%, 0.01 wt%, 0.1 wt%, 1 wt%, 5 wt%, 10 wt% and / or less than about 30 wt%, 25 wt%, 20 wt%, 15 wt%, 10 wt%, 9 wt%, 8 wt%, 7 wt%, 6 wt%, 5 wt%, 4 wt%, 3 wt%, 2 wt%, 1 wt% or a combination thereof, including, for example, 0.1 wt% to 10 wt%, based on the total weight of the cover layer.
[0077] The adsorbent may be dispersed on the fiber container laminated with the spunbond nonwoven by a dispersing device. The adsorbent may be dispersed by several dispersing devices. In one embodiment, the adsorbent is dispersed by one dispersing device. If the adsorbent is dispersed by multiple dispersing devices, the first dispersed adsorbent may clog the holes on the surface of the fiber container and prevent the subsequent dispersed adsorbent from entering the interior of the fiber container. A brush or a vibrating device may be used to help the dispersed adsorbent enter the interior of the fiber container.
[0078] In one embodiment, after the sorbent is dispersed on the fiber container, a brushing technique may be used (e.g., 2 to 3 times) to help the sorbent penetrate into the pores of the fiber container. Smaller sorbent particles may fall into or be pushed further into the fiber container, and larger sorbent particles may remain on or toward the top of the fiber container.
[0079] For example, a hot melt powder adhesive, a hot melt web adhesive, or a combination thereof can be provided to a fiber container containing an adsorbent to laminate a fiber container containing an adsorbent and a covering layer. The hot melt powder can be used in an amount less than or equal to 10 wt % based on the total adsorbent weight. The hot melt powder can be made of: polyurethane (PU), PET, ethylene vinyl acetate (EVA), polyamide (PA) or a copolymer thereof. The hot melt powder can have a diameter of 0.1 mm to 0.4 mm. The hot melt powder can have a melting point of 70°C to 160°C. The hot melt powder adhesive can bond the adsorbent located on the surface of the fiber container. In one embodiment, the hot melt powder can have a viscosity greater than 0 g / m 2 Up to 60 30g / m 2 The basis weight.
[0080] In one embodiment, the fiber container includes an amount greater than 0 wt% and less than 10 wt% of binder based on the total weight of the adsorbent. In one embodiment, the fiber container includes less than 1 wt%, for example, 0 wt%, of binder based on the total weight of the adsorbent.
[0081] The hot melt web adhesive may have a 5 g / m 2 Up to 30g / m 2 , for example, 10g / m 2 The hot melt web adhesive may include polyurethane PU, EVA, polyamide PA, PET or copolymers thereof. The hot melt web adhesive may bond the adsorbent layer and the cover layer.
[0082] The cover layer laminated with the adsorbent layer can be the same nonwoven used for lamination with the fiber container.If additional lamination with a filtration efficiency layer (such as meltblown) is desired, another cover layer lighter than the first cover layer can be used.
[0083] The final filter medium can be formed by lamination, for example, the layers can be heated and bonded together. For example, a flat-bed laminator can be used. The lamination process can be controlled by adjusting the machine speed (e.g., 3 meters per minute (m / min) to 10 meters per minute), temperature (e.g., 130° C. to 200° C.), and pressure (e.g., 0 megapascals (MPa) to 5 MPa). The final filter medium can be formed with or without a calendering step. During lamination (e.g., a belt dry lamination process), the adsorbent may enter the fiber container or move further within the fiber container.
[0084] In one embodiment, one or more additional layers of the filter media may include an "efficiency layer" to obtain higher particle filtration efficiency. The efficiency layer may include, for example, nanofibers, meltblown fibers, expanded polytetrafluoroethylene (ePTFE) membranes, electrically charged needle felts, nonwovens containing microglass fibers, or combinations thereof. In one embodiment, the efficiency layer may have a basis weight of 15 g / m2 to 30 g / m2 and include PP meltblown fibers. In one embodiment, the efficiency layer includes an electrostatically charged layer, for example, an electrostatically charged meltblown nonwoven.
[0085] The filter medium can have a density of 700 g / m 2 Up to 1,390g / m 2 For example, a base weight of 700 g / m 2 The basis weight of the filter media may include 500 g / m 2 The adsorbent has no efficiency layer and has a 1,390 g / m 2 The basis weight of the filter media may include 1,000 g / m 2 The adsorbent has an efficiency layer.
[0086] The filter medium can have a thickness greater than or equal to 2.0 mm, for example, greater than or equal to 2.4 mm. The indicated thickness can be the stacking direction of the open phase on the second phase. The filter medium can have a thickness less than or equal to 4.0 mm, for example, less than 2.5 mm, and the fiber container can have a thickness greater than or equal to 3.5 mm. Thinner filter media provide lower air permeability of the filter medium, and thicker filter media provide higher air permeability of the filter medium. In one embodiment, the filter medium has a thickness less than 2.5 mm to assist pleating. Filter media with a thickness greater than 2.5 may be difficult to pleat.
[0087] Depending on the efficiency layer, the air permeability of the filter media may be 5 cubic feet per minute (cfm) to 200 cfm. For example, an efficiency layer including meltblown fibers may have low air permeability and may reduce the overall air permeability of the filter media.
[0088] In order to prevent the fiber container from delaminating from the adjacent cover layer or further layers, an adhesive web may be added between the fiber container and the adjacent cover layer or further layers. The adhesive web may have a viscosity of 5 g / m 2 Up to 30g / m 2 , for example, 10g / m 2 Exemplary adhesive webs may include PU, EVA, PA, PET, or copolymers thereof.
[0089] The filter media can be configured to be used as a fuel cell intake filter. The filter media can filter particles to limit the clogging of channels and proton exchange membranes in the fuel cell. The filter media can remove volatile organic compounds (VOCs), SO2, NOx, NH3, or a combination thereof, and extend the life of the catalyst (e.g., platinum) of the fuel cell and improve the service interval of the fuel cell. For example, the disclosed filter media may be suitable for applications including intake filter media for fuel cells for electric vehicles (EVs).
[0090] The filter media can be configured to filter automotive cabin air, for example, the disclosed filter media can be suitable for applications including cabin filter media for EVs. The filter media can be configured to filter particles (such as dust, pollen, smoke, bacteria, and particulate matter 2.5 (PM2.5)), gases (such as ozone, benzene, sulfur oxides (SOx), and NOx), odors, or combinations thereof from cabin air.
[0091] The air filter media can be configured to act as an automotive engine intake filter, which can be configured to filter particulate matter (such as dust, pollen, smoke, bacteria, and PM2.5) from the air entering the engine of the vehicle. The air filter media can be configured to be used in gas turbine intake filters, air-oil separation filters (for example, in compressed air applications), air pollution control and dust collection filter elements (such as can be used to reduce or eliminate particulate emissions from industrial sources into the atmosphere) or heating, ventilation and air conditioning (HVAC) filter elements, etc. The air filter media can be configured to act as an HVAC molecular filter. The air filter media can be configured to act as an indoor air purifier.
[0092] Thus, a gas adsorption filter, a cabin air filter for a vehicle, an air intake filter for a vehicle, or a heating, ventilation, and air conditioning filter may include the disclosed filter media.Depending on the end use of the product, the filtering characteristics and properties of the disclosed filter media may vary.
[0093] The present disclosure is further illustrated by the following non-limiting examples.
[0094] Example
[0095] Comparative Examples
[0096] The comparative example included activated carbon and a hot melt spray adhesive for bonding the activated carbon particles and the laminate nonwoven layers. Figure 1 is a SEM image of the filter medium of the comparative example, and Figure 2 is an enlarged SEM image of the filter medium of Comparative Example.
[0097] Example 1
[0098] Will include 25g / m 2 PET fiber spunbond nonwoven with 5g / m 2 Hot melt powder adhesive laminated to 90g / m 2 The fiber container has a basis weight of 150 wt % of bicomponent PET fiber and 50 wt % of bicomponent PET fiber. The second phase of the fiber container includes 30 wt % of bicomponent PET fiber and 70 wt % of bicomponent PET fiber. The weight of the open phase and the second phase are each 45 g / m 2 .
[0099] Fiber container including 700g / m 2 Activated carbon particles impregnated with 3 wt% KI (potassium iodide) were prepared. The impregnated activated carbon had a size of 30 to 80 mesh. After adding the activated carbon particles, another 25 g / m 2 A PET fiber spunbond nonwoven is laminated to the opposite surface of the fiber container. For the lamination of the cover layer, a 60 g / m 2 Hot melt powder adhesive made of PET copolymer (co-PET) and 10g / m 2 Hot melt web adhesive made from co-PET.
[0100] With 30g / m 2 An E10 grade meltblown nonwoven with a basis weight of 1000 Å and including PP meltblown fibers was used as the efficiency layer. The efficiency layer had an efficiency of 86.2% at 0.3 micron NaCl test aerosol at 32 LPM test air flow rate. The meltblown nonwoven was laminated with a hot melt web adhesive made of co-PET.
[0101] Example 2
[0102] Will include 25 g / m2 (g / m 2 ) of polyethylene terephthalate (PET) fiber spunbond nonwoven fabric with 5g / m 2Hot melt powder adhesive laminated to 90g / m 2 The fiber container has a basis weight of 15 g / m2. The open phase of the fiber container includes 50 weight percent (wt%) of 15 denier bicomponent PET fiber and 50 wt% of 6 denier bicomponent PET fiber. The second phase of the fiber container includes 30 wt% of 15 denier bicomponent PET fiber and 70 wt% of 6 denier bicomponent PET fiber. The weight of the open phase and the second phase are each 45 g / m2. 2 .
[0103] Fiber container including 500g / m 2 The activated carbon particles impregnated with 3wt% KI and 200g / m 2 After adding the activated carbon particles, another 25 g / m 2 was added using a flat-bed laminator at a machine speed of 4 meters per minute (m / min), a laminator temperature of 160° C. to 190° C., and a laminating pressure of 4 megapascals (MPa). 2 A PET fiber spunbond nonwoven is laminated to the opposite surface of the fiber container. For the lamination of the cover layer, a 60 g / m 2 Hot melt powder adhesive made of co-PET and 10g / m 2 Hot melt web adhesive made from co-PET.
[0104] With 30g / m 2 A grade H13 meltblown nonwoven with a basis weight of 1000 Å and including PP meltblown fibers was used as the efficiency layer. The efficiency layer had an efficiency of 99.97% at 0.3 micron NaCl test aerosol at 32 LPM test air flow rate. The meltblown nonwoven was laminated with a hot melt web adhesive made of co-PET.
[0105] Figure 3 is a scanning electron microscope (SEM) image of the filter medium of Example 2; Figure 4 is an enlarged SEM image of the filter medium of Example 2; Figure 5 is a SEM image of fibers included in the open phase of the fiber container of the filter medium of Example 2; Figure 6 is an enlarged SEM image of fibers included in an open phase of a fiber container of the filter medium of Example 2; Figure 7 is a SEM image of fibers included in the second phase of the fiber container of the filter medium of Example 2; and Figure 8 is an enlarged SEM image of fibers included in the second phase of the fiber container of the filter medium of Example 2.
[0106] Example 3
[0107] Example 3 includes 560 g / m 2The activated carbon particles impregnated with 3wt% KI and 140g / m 2 Dry ion exchange resin with polystyrene and divinylbenzene moieties and sulfonic acid functional groups.
[0108] The physical properties of Examples 1 to 3 and the Comparative Examples are provided in Table 1.
[0109] Table 1
[0110]
[0111]
[0112] Fig. 9 is a graph of n-butane (nB) penetration (percent (%)) versus time (minutes (min)), showing nB adsorption rates of filter media of Example 1 and Comparative Examples; Fig.10 is a graph of toluene penetration (%) versus time (minutes), showing toluene adsorption rates of filter media of Example 1 and Comparative Example; Fig.11 is a graph of SO2 penetration (%) versus time (minutes) showing the SO2 adsorption rates of the filter media of Example 1 and Comparative Example; and Fig.12 is a graph of NO2 penetration (%) versus time (minutes), showing the NO2 adsorption rates of the filter media of Example 1 and Comparative Example.
[0113] Compared to the comparative example including a larger loading of activated carbon particles, Example 1 exhibited better performance in the adsorption rates of n-butane and NO2, and exhibited similar performance in the adsorption rates of toluene and SO2.
[0114] Fig.13 is a graph of nB penetration (%) versus time (min), showing nB adsorption for the filter media of Example 2; Fig.14 is a graph of toluene penetration (%) versus time (minutes), showing the toluene adsorption rate of the filter medium of Example 2; Fig.15 is a graph of SO2 penetration (%) versus time (minutes), showing the SO2 adsorption rate of the filter medium of Example 2; Fig.16 is a graph of NO2 penetration (%) versus time (minutes), showing the NO2 adsorption rate of the filter medium of Example 2; Fig.17 is a graph of nitrogen oxide (NOx) penetration (%) versus time (minutes), illustrating the NOx adsorption rate of the filter medium of Example 2; and Fig.18 is a graph of NH 3 penetration (%) versus time (minutes), showing the NH 3 adsorption rate of the filter medium of Example 2.
[0115] Fig.19 is a graph of SO2 penetration (%) versus time (minutes), showing the SO2 adsorption rate of the filter medium of Example 3; Fig. 20 is a graph of NOx and NO2 penetration (%) versus time (minutes), illustrating the NOx and NO2 adsorption rates of the filter media of Example 3; and Fig.21 is a graph of NH 3 penetration (%) versus time (minutes), showing the NH 3 adsorption rate of the filter medium of Example 3.
[0116] Fig. 22 is a graph of NH3 penetration (%) versus time (minutes), showing a comparison of the NH3 adsorption rates of the filter media of Example 2 and Example 3. Fig. 22 The technical benefit of using ion exchange resins on NH3 adsorption rate is demonstrated.
[0117] The present disclosure further encompasses the following aspects.
[0118] Aspect 1. A filter medium, comprising: a fiber container, wherein the fiber container comprises
[0119] an open phase and a second phase disposed on the open phase; and an adsorbent disposed within the fiber container, wherein each of the open phase and the second phase comprises thicker fibers and thinner fibers, and wherein the average diameter of the fibers in the open phase is greater than the average diameter of the fibers in the second phase.
[0120] Aspect 2. The filter media of aspect 1, wherein the average pore size of the open phase is greater than the average pore size of the second phase.
[0121] Aspect 3. The filter media of Aspect 1 or 2, wherein the proportion of the thicker fibers in the open phase is less than or equal to the proportion of the thinner fibers in the open phase.
[0122] Aspect 4. The filter media of any one or more of the preceding aspects, wherein the proportion of the thicker fibers in the second phase is less than the proportion of the thinner fibers in the second phase.
[0123] Aspect 5. The filter media of any one or more of the preceding aspects, wherein the proportion of the thicker fibers in the open phase is greater than the proportion of the thicker fibers in the second phase.
[0124] Aspect 6. The filter media of any one or more of the preceding aspects, wherein the proportion of the thinner fibers in the open phase is less than the proportion of the thinner fibers in the second phase.
[0125] Aspect 7. The filter media of any one or more of the preceding aspects, wherein the thicker fibers are present in the open phase in an amount of 30 wt % to 50 wt %, based on the total fiber weight of the open phase.
[0126] Aspect 8. The filter media of any one or more of the preceding aspects, wherein the thicker fibers comprise fibers of 15 denier to 20 denier.
[0127] Aspect 9. The filter media of any one or more of the preceding aspects, wherein the thinner fibers are present in the open phase in an amount of 50 wt % to 70 wt % based on the weight of the fibers in the open phase.
[0128] Aspect 10. The filter media of any one or more of the preceding aspects, wherein the thinner fibers comprise fibers of 5 denier to less than 10 denier or fibers of 7 denier to less than 10 denier.
[0129] Aspect 11. The filter media of any one or more of the preceding aspects, wherein the thicker fibers are present in the second phase in an amount of 10 wt % to 20 wt % based on the weight of the fibers of the second phase.
[0130] Aspect 12. The filter media of any one or more of the preceding aspects, wherein the thinner fibers are present in the second phase in an amount of 80 wt % to 90 wt % based on the weight of the fibers of the second phase.
[0131] Aspect 13. The filter media of any one or more of the preceding aspects, wherein the thicker fibers comprise polyethylene terephthalate fibers.
[0132] Aspect 14. The filter media of any one or more of the preceding aspects, wherein the thinner fibers comprise polyethylene terephthalate fibers.
[0133] Aspect 15. The filter media of any one or more of the preceding aspects, wherein the fiber container comprises a binder in an amount greater than 0 wt % and less than 10 wt % based on the total weight of the adsorbent.
[0134] Aspect 16. The filter media of any one or more of aspects 1 to 14, wherein the fiber container comprises less than 1 wt % or 0 wt % binder based on the total weight of the adsorbent.
[0135] Aspect 17. The filtration medium according to any one or more of the preceding aspects, wherein the adsorbent comprises activated carbon particles, silica, zeolite, molecular sieves, clay, alumina, sodium bicarbonate, ion exchange resin, a catalyst, or a combination thereof.
[0136] Aspect 18. The filter medium of aspect 17, wherein the adsorbent comprises activated carbon particles, impregnated activated carbon particles, ion exchange resin, or a combination thereof.
[0137] Aspect 19. The filter medium of any one or more of the preceding aspects, further comprising a cover layer.
[0138] Aspect 20. The filter media of aspect 19, wherein the cover layer comprises spunbond fibers.
[0139] Aspect 21. The filter media of aspect 19 or 20, further comprising a binder, wherein the binder is present only at the interface between the fiber container and the cover layer.
[0140] Aspect 22. The filter media of any one or more of the preceding aspects, having a thickness less than or equal to 4.0 mm.
[0141] Aspect 23. The filter media of any one or more of the preceding aspects, having a thickness of less than 2.5 mm.
[0142] Aspect 24. The filter media of any one or more of the preceding aspects, wherein the filter media is pleated.
[0143] Aspect 25. A gas adsorption filter comprising the filter medium according to any one or more of the preceding aspects.
[0144] Aspect 26. A cabin air filter for a vehicle, the cabin air filter comprising the filter medium according to any one or more of the preceding aspects.
[0145] Aspect 27. An air intake filter for a vehicle, the air intake filter comprising the filter medium according to any one or more of the preceding aspects.
[0146] Aspect 28. A heating, ventilation, and air conditioning filter comprising the filter media according to any one or more of the preceding aspects.
[0147] Aspect 29. The filter medium of any one or more of the preceding aspects, formed by a process comprising: forming the fiber container; providing the adsorbent onto the fiber container; and laminating the fiber container to form the filter medium.
[0148] Aspect 30. The filter media of aspect 29, wherein the process further comprises providing an adhesive to the fiber container after adding the adsorbent to the fiber container.
[0149] Aspect 31. The filter media of Aspect 30, wherein the binder comprises a powder.
[0150] Aspect 32. The filter media of Aspect 30 or 31, wherein the adhesive comprises a web.
[0151] Aspect 33. The filter media of any one or more of Aspects 30 to 32, wherein the binder is not present in the second phase.
[0152] Aspect 34. The filter media of any one or more of Aspects 30 to 32, wherein less than 1 wt % binder is present in the second phase based on the total weight of the second phase.
[0153] Aspect 35. The filter media of any one or more of Aspects 30 to 34, wherein forming the fiber receptacles comprises intermixing the thicker fibers and the thinner fibers in the open phase and the second phase.
[0154] Although specific embodiments have been described, the applicant or other persons skilled in the art may think of substitutions, modifications, variations, improvements, and substantial equivalents that are currently or possibly not yet foreseeable. Therefore, the appended claims, as submitted and as may be amended, are intended to cover all such substitutions, modifications, variations, improvements, and substantial equivalents.
[0155] It should be understood that when an element is referred to as being "on another element," it can be directly on the other element or intervening elements may exist between the two elements. In contrast, when an element is referred to as being "directly on another element," there are no intervening elements.
[0156] All ranges disclosed herein include end values, and the end values can be independently combined with each other (for example, the range of "up to 25wt%, or more specifically, 5wt% to 20wt%" includes end values and all intermediate values within the range of "5wt% to 25wt%", etc.). "Combination" includes blends, mixtures, alloys, reaction products, etc. The terms "first", "second", etc. do not indicate any order, quantity, or importance, but are used to distinguish one element from another. Unless otherwise specified herein or clearly contradictory to the context, the terms "one (a)" and "an" and "the" do not represent restrictions on quantity and should be interpreted as covering both singular and plural. Unless otherwise explicitly stated, "or" means "and / or". References to "some embodiments", "one embodiment", etc. throughout the specification mean that the specific elements described in conjunction with the embodiment are included in at least one embodiment described herein, and may or may not be present in other embodiments. In addition, it should be understood that the described elements can be combined in any suitable manner in various embodiments. "Combinations thereof" are open ended and include any combination comprising at least one of the listed components or properties, optionally with similar or equivalent components or properties that are not listed.
[0157] As shown in the accompanying drawings, relative terms such as "lower" or "bottom" and "upper" or "top" may be used herein to describe the relationship of one element to another element. It should be understood that relative terms are intended to cover different orientations of the device in addition to the orientation depicted in the accompanying drawings. For example, if the device in one of the drawings is turned over, the element described as being located on the "lower side" of the other elements will then be oriented on the "upper side" of the other elements. Therefore, depending on the specific orientation of the drawings, the exemplary term "lower" can cover both the lower orientation and the upper orientation. Similarly, if the device in one of the drawings is turned over, the element described as being located "below" or "below" the other elements will then be oriented "above" the other elements. Therefore, the exemplary terms "below" or "below" can cover both the upper orientation and the lower orientation.
[0158] Unless otherwise defined, technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which this application belongs. All cited patents, patent applications, and other references are incorporated herein by reference in their entirety. However, if a term in this application contradicts or conflicts with a term in an incorporated reference, the term from this application takes precedence over the conflicting term from the incorporated reference.
[0159] Unless otherwise specified herein, all test standards are the most current standards in effect as of the filing date of this application, or, if priority is claimed, the filing date of the earliest priority application in which the test standards appear.
[0160] Although the filter media and methods of the present disclosure have been described with reference to exemplary embodiments of the present disclosure, the present disclosure is not limited to such exemplary embodiments and / or implementations.
[0161] The nature and method are susceptible to many implementations and applications, which will be apparent to those skilled in the art from this disclosure. This disclosure expressly covers such modifications, enhancements and / or
[0162] As many changes could be made in the above constructions, and many widely different embodiments of the disclosure could be made without departing from the scope thereof, it is intended that all matter contained in the accompanying drawings and description shall be interpreted as illustrative and not limiting.
[0163] Additional modifications, changes, and substitutions. Therefore, it should be understood that the appended claims should be interpreted broadly and in a manner consistent with the scope of the present disclosure.
Claims
1. A filter medium, comprising: A fiber container comprising Open phase, and a second phase located on the open phase; and an adsorbent, the adsorbent being located within the fiber container, wherein each of the open phase and the second phase comprises thicker fibers and thinner fibers, and The average diameter of the fibers in the open phase is greater than the average diameter of the fibers in the second phase. 2 . The filter medium of claim 1 , wherein the average pore size of the open phase is greater than the average pore size of the second phase.
3. The filter medium of claim 1 or 2, wherein the proportion of the thicker fibers in the open phase is less than or equal to the proportion of the thinner fibers in the open phase.
4. The filter medium of any one or more of the preceding claims, wherein the proportion of the thicker fibers in the second phase is less than the proportion of the thinner fibers in the second phase.
5. The filter medium of any one or more of the preceding claims, wherein the proportion of the thicker fibers in the open phase is greater than the proportion of the thicker fibers in the second phase.
6. A filter medium according to any one or more of the preceding claims, wherein the proportion of the thinner fibers in the open phase is less than the proportion of the thinner fibers in the second phase.
7. The filter media of any one or more of the preceding claims, wherein the thicker fibers are present in the open phase in an amount of 30% to 50% by weight, based on the total fiber weight of the open phase.
8. The filter media of any one or more of the preceding claims, wherein the thicker fibers comprise fibers of 15 denier to 20 denier.
9. The filter medium of any one or more of the preceding claims, wherein the thinner fibers are present in the open phase in an amount of 50% to 70% by weight, based on the weight of the fibers of the open phase.
10. The filter media of any one or more of the preceding claims, wherein the thinner fibers comprise fibers of 5 denier to less than 10 denier or fibers of 7 denier to less than 10 denier.
11. The filter media of any one or more of the preceding claims, wherein the thicker fibers are present in the second phase in an amount of 10% to 20% by weight, based on the weight of the fibers of the second phase.
12. The filter media of any one or more of the preceding claims, wherein the thinner fibers are present in the second phase in an amount of 80% to 90% by weight, based on the weight of the fibers of the second phase.
13. The filter media of any one or more of the preceding claims, wherein the thicker fibers comprise polyethylene terephthalate fibers.
14. The filter media of any one or more of the preceding claims, wherein the thinner fibers comprise polyethylene terephthalate fibers.
15. The filter medium of any one or more of the preceding claims, wherein the fiber container comprises a binder in an amount greater than 0 wt% and less than 10 wt%, based on the total weight of the adsorbent.
16. The filter medium of any one or more of claims 1 to 14, wherein the fiber container comprises less than 1 wt% or 0 wt% binder based on the total weight of the adsorbent.
17. The filter medium of any one or more of the preceding claims, wherein the adsorbent comprises activated carbon particles, silica, zeolites, molecular sieves, clays, alumina, sodium bicarbonate, ion exchange resins, catalysts, or combinations thereof.
18. The filter media of claim 17, wherein the adsorbent comprises activated carbon particles, impregnated activated carbon particles, ion exchange resins, or combinations thereof.
19. The filter medium of any one or more of the preceding claims, further comprising a cover layer.
20. The filter media of claim 19, wherein the cover layer comprises spunbond fibers.
21. The filter media of claim 19 or 20, further comprising a binder, wherein the binder is present only at the interface between the fiber container and the cover layer.
22. The filter medium of any one or more of the preceding claims, having a thickness less than or equal to 4.0 mm.
23. Filter medium according to any one or more of the preceding claims, having a thickness of less than 2.5 mm.
24. The filter medium of any one or more of the preceding claims, wherein the filter medium is pleated.
25. A gas adsorption filter comprising a filter medium according to any one or more of the preceding claims.
26. A cabin air filter for a vehicle, the cabin air filter comprising a filter medium according to any one or more of the preceding claims.
27. An air intake filter for a vehicle, the air intake filter comprising a filter medium according to any one or more of the preceding claims.
28. A heating, ventilation and air conditioning filter comprising a filter medium according to any one or more of the preceding claims.
29. The filter medium of any one or more of the preceding claims, formed by a process comprising: forming the fiber container; providing the adsorbent onto the fiber container; and The fiber containers are laminated to form the filter media.
30. The filter media of claim 29, wherein the process further comprises providing an adhesive to the fiber container after adding the adsorbent to the fiber container.
31. The filter media of claim 30, wherein the binder comprises a powder.
32. The filter media of claim 30 or 31, wherein the adhesive comprises a web.
33. The filter medium of any one or more of claims 30 to 32, wherein the binder is absent from the second phase.
34. The filter media of any one or more of claims 30 to 32, wherein less than 1 wt% binder is present in the second phase, based on the total weight of the second phase.
35. The filter media of any one or more of claims 30-34, wherein forming the fiber receptacles comprises intermixing the thicker fibers and the thinner fibers in the open phase and the second phase.